Organoleptic Characteristics of Nastar Broccoli with Podang Mango Jam as a Healthy Snack Innovation for Pregnant Women: Karakteristik Organoleptik Nastar Brokoli Selai Mangga Podang Sebagai Inovasi Cemilan Sehat Pada Ibu Hamil - Ulilalbab, Arya; Santi, Sherly Maureta; Sari, Ria Novita; Putri, Riska Nabela Andini; Zahroh, Ummu; Anshori, Zahwa Annisa (jurnal makanan tropis dan teknologi agroindustri, 2023)
A woman who is in pregnancy from conception to birth is called a pregnant woman. Pregnant women can be at risk of anemia due to the impact of folic acid deficiency. Alternative innovations in healthy snack products for pregnant women include pineapple cakes, which are innovated with broccoli which is rich in folic acid and mango podang. The type of method of this research is experiments using organoleptic tests where researchers measure the level of preference for processed products from broccoli flour 3 treatments P1 (100% wheat flour: 0% broccoli flour), P2 (96.5% wheat flour: 3 broccoli flour, 5%) and P3 (93% wheat flour, 7% broccoli flour).The results showed that the highest acceptability of this product to color was P1 (97%), the highest aroma acceptability was P1 (97%), the highest texture acceptability was P1 (95%), and the highest taste acceptability was P1 (98%). This is because the P1 dough has not been mixed with broccoli flour so that in terms of color, aroma, texture and taste it has superior results, but the difference in the percentage of acceptability with P2 and P3 is not much different.